Binding and Unbinding the Mondrian Stimulus. (27th October 2018) - Davis, Whitney
Abstract: This paper considers the use of the 'Mondrian Stimulus', invented by Edwin H. Land of the Polaroid Corporation, in various investigations in the visual neuropsychology, the neuroaesthetics, and the social psychology of aesthetic response to works of visual art (notably, investigations by Semir Zeki and A. Michael Noll). What difference does it make—in the set-up of these investigations and in our interpretation of their putative results—that the Mondrian Stimulus might be taken to be a 'real' painting by the actual Dutch artist Piet Mondrian? How does the existence of a set of 'real' Mondrians—more or less well known to many people, including those investigated in experiments by Land, Zeki, and Noll—affect the ways in which the Mondrian Stimulus is apprehended? The paper argues that the Mondrian Stimulus is 'bound' to the history and visual recollection of 'real Mondrians' at the same time as the 'real Mondrians'—in their historical afterlives—are bound to other creations of 'modern abstract art'. These proposals enable a revised approach to the relations between invariant visual responses (such as Land and Zeki derived for colour vision) on the one hand, and different visual cultures or visuality on the other; because of its own special history of 'binding' and 'unbinding', the Mondrian Stimulus works as an interface between—a binding of—both 'bottom-up' perceptual input and processing and 'top-down' direction of attention.